Postcolonial Aesthetics: Talempong Kreasi and Talempong Goyang in West Sumatra - Andar Indra Sastra; Nadya Fulzi; Syahri Anton (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
The aim of this article is to disclose the postcolonial aesthetics of talempong kreasi and talempong goyang in West Sumatra. Aesthetics can be defined as a sense of perception or the various kinds of feelings that are aroused by an art object that is being observed. Postcolonialism is understood to be the continuation of colonialism; hence postcolonial aesthetics discusses the sense of perception, in this case with reference to talempong kreasi and talempong goyang as the material object. Talempong is a type of bronze musical instrument found in West Sumatra; the word kreasi means ‘creation’ or something new, while the word goyang means ‘rocking’ or ‘swaying’ and refers to the body movements of the spectators as they appear to dance in time to the talempong music. The addition of the words kreasi and goyang after the word talempong create the impression that this type of music belongs to the domain of popular music. The emergence of these two concepts in West Sumatra cannot be separated from the influence and power of a number of leading figures in the field of education – specifically artists – from the colonial era, who had a background in Western music education. Talempong kreasi and talempong goyang are dynamic in nature and have the ability to play both major and minor melodies as the talempong instruments are tuned to chromatic pitches. The tuning system of the talempong is akin to that of diatonic musical instruments, and as a musical system it presents the harmonies of Western music through its melodies and chords. The problem to be addressed in this article focuses on postcolonial aesthetics, with talempong kreasi and talempong goyang in West Sumatra as the material object of the study. This phenomenon is examined using the postcolonial theory, relying on qualitative data which is supported by additional qualitative data. The results of the research show that talempong kreasi and talempong goyang in West Sumatra are a product of postcolonialism.